PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Pradana, Era Yunian; Handayani, Nur (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
This research aimed to examine the effect of Local-Owned Source revenue, General Allocation Fund, and Special Allocation Fund on the financial performance of local government in districts/cities of East Java Province. The research was quantitative. Moreover, the data collection technique used total sampling i.e., all the population members were the sample. In line with that, there were 38 districts/cities of East Java Province during the observation period of 2019-2021. Furthermore, the data were from the realization of regional income and expenditure budgets statement for all districts/cities in East Java Province and were taken from the Financial Audit Agency of East Java Province. Moreover, the data analysis technique used multiple linear regressions with SPSS 26. The result showed that (1) Local-Owned Source revenue had a positive effect on the financial performance of local government in districts/cities of East Java Province, (2) General Allocation Fund did not affect the financial performance of local government in districts/cities of East Java Province, and 3) Special Allocation Fund had a negative effect on the financial performance of local government in districts/cities of East Java Province.